Răspuns:
a)
[tex](\frac{4}{9})^{5} =(\frac{2^{2} }{3^{2} })^{5} =(\frac{2}{3})^{2*5} =(\frac{2}{3})^{10}[/tex]
[tex](\frac{25}{36})^{11} =(\frac{5^{2} }{6^{2} })^{11} =(\frac{5}{6})^{2*11} =(\frac{5}{6})^{22}[/tex]
b)
[tex](\frac{8}{27})^{4} =(\frac{2^{3} }{3^{3} })^{4} =(\frac{2}{3})^{3*4} =(\frac{2}{3})^{12}[/tex]
[tex](\frac{125}{216})^{12} =(\frac{5^{3} }{6^{3} })^{12} =(\frac{5}{6})^{3*12} =(\frac{5}{6})^{36}[/tex]
c)
[tex](\frac{1}{9})^{12} =(\frac{1^{2} }{3^{2} })^{12} =(\frac{1}{3})^{2*12} =(\frac{1}{3})^{24}[/tex]
[tex](\frac{1}{27})^{8} =(\frac{1^{3} }{3^{3} })^{8} =(\frac{1}{3})^{3*8} =(\frac{1}{3})^{24}[/tex]
Explicație pas cu pas: